Kondisi Empati Dasar Mahasiswa Bimbingan dan Konseling Se-DKI Jakarta - Happy Karlina Marjo (Psiko-Edukasi, 2015)
The research objective is to identify the conditions of basic empathy student Counseling in DKI Jakarta. This research used a descriptive study with 294 sample of students counseling from 5 universities in Jakarta; Universitas Negeri Jakarta (UNJ), Universitas Muhammadiyah Prof. Dr Hamka Jakarta (UHAMKA), Universitas Islam As-Syafi'iyah Jakarta, Universitas  Atma Jaya and Universitas Kristen Indonesia (UKI). The research instrument used Basic Empathy Scale (BES) from Jollive & David (2006) with r 0.857.  The analysis of the level of basic empathy was in percentage (descriptive analysis) with SPSS version 20. This study has found condition of basic empathy of students counseling in Jakarta at the high level category of 16.91%, middle category of 67.98%, and 15.11% lower. From these findings indicate necessary to improvement and development of basic empathy students' condition.